2011
DOI: 10.1111/j.1463-5224.2011.00898.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mydriasis induced by topical instillations of 0.5% tropicamide on the anterior segment in normotensive dogs using ultrasound biomicroscopy

Abstract: Mydriasis induced by topical 0.5% tropicamide results in modification of the anterior segment which may influence the drainage of aqueous humor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 25 publications
1
27
0
Order By: Relevance
“…This study also reported that the ACD increase could also be detected using an A-scan ultrasonographic examination (34) . Finally, an animal study performed using UBM also reported an increase in ACA values following mydriasis (using 0.5% tropicamide) (35) . Here, the increase in ACA and ACV following pharmacological dilation was attributed to the backward movement of the iris lens diaphragm as a result of longitudinal ciliary muscle contraction (32) .…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported that the ACD increase could also be detected using an A-scan ultrasonographic examination (34) . Finally, an animal study performed using UBM also reported an increase in ACA values following mydriasis (using 0.5% tropicamide) (35) . Here, the increase in ACA and ACV following pharmacological dilation was attributed to the backward movement of the iris lens diaphragm as a result of longitudinal ciliary muscle contraction (32) .…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent ocular pregnancy onward. [26][27][28][29][30][31][32][33][34] Recent advancements in biomicroscopy transducer design allows for imaging without the use of cumbersome water baths and general anesthesia as described in initial veterinary reports. 62 The postnatal development of corneal thickness in cats measured by ultrasound biomicroscopy has also been reported.…”
Section: General Considerations B-mode Examinationmentioning
confidence: 99%
“…62 The postnatal development of corneal thickness in cats measured by ultrasound biomicroscopy has also been reported. [29][30][31]33,34 [26][27][28][29][30][31][32][33][34] Recent advancements in biomicroscopy transducer design allows for imaging without the use of cumbersome water baths and general anesthesia as described in initial veterinary reports.…”
Section: General Considerations B-mode Examinationmentioning
confidence: 99%
See 2 more Smart Citations